Asceticism as a Driving Factor of Marriage: Study of Marriage Syar'i Hijab Student - Fauziyah, Umi Nur; Suhartini, Elly (Jurnal ENTITAS SOSIOLOGI, 2019)
Asceticism is the desire to be blessed to be closer to the creator. Asceticism can be a motivation for Marriage at a young age. Marriage is often interpreted as something very crucial for humans. This study aims to determine the reasons for marriages conducted by Shari hooded female students by using Peter L. Berger and Thomas Luckman's social construction theory. This study uses qualitative research methods with a constructivist approach. The results showed that asceticism was the main factor causing marriages among Shari veiled female students. Other factors are obedience to parents, obedience to husband, happiness, norms, and rizq obtained, involvement in religious activities. The decision to get married chosen by students has a positive and negative impact on life lived both in the academic field and in everyday life. Keywords: asceticism, syari students, marriage. Referensi: Carl W Ernist, The Shambala Guide to Sufism. Shambala Publication Inc., Boston, 1997. Hadiwijono, Harun, Seri Sejarah Filsafat Barat I. Kanisius,Yogyakarta, 1980 IAIN Syarif Hidyatullah, ”Zuhud" dalam Insklopedi Islam Indonesia. Djambatan, Jakarta, 1992. Jones, P. (2009). Pengantar Teori-Teori Sosial. Jakarta: Yayasan Pustaka Obor Indonesia. Koentjaraningrat. (1990). Manusia dan Kebudayaan di Indonesia. Jakarta: Djambatan. Liliweri, A. (1996). Sosiologi Organisasi. Bandung: Citra Aditya Bakti. Luckman, P. L. (1990). Tafsir Sosial atas Kenyataan. Jakarta: LP3ES. Margono, S. (2007). Metodologi Penelitian Pendidikan. Jakarta: Rineka Cipta. Norman K. Denzin, Y. S. (2009). Handbook of Qualitative Research. Yogyakarta: Pustaka Pelajar. Ritzer, G. (2014). Teori Sosiologi Modern. Jakarta: PRENADAMEDIA GROUP. ------------(2014). Sosiologi Ilmu Pengetahuan Berparadigma Ganda. Depok: RajaGrafindo Persada . Shiraishi, S. S. (2009). Pahlawan-Pahlawan Belia. Bogor: Grafika Mardi Yuana. Soekanto, S. (2012). Sosiologi Suatu Pengantar. Jakarta: Kharisma Putra Utama Offset. Sugiyono. (2014). Metode Penelitian Kuantitatif Kualitatif dan R&B. Bandung: Alfabeta. Thoreau, H. D. (1854). Walden; or, Life in the Wooda. Boston: Ticknour and Fields. Weber, M. (2002). Teori Dasar Analisis Kebudayaan. Jogjakarta: IRCiSoD. Jurnal: Agustian, H. (2013). Gambaran kehidupan pasangan yang menikah di usia muda di Kabupaten Dharmasraya. Spektrum PLS, Vol. 1(1), 205-217. Anisaningtyas, G., & Dwi, A. Y. (2011). Pernikahan di Kalangan Mahasiswa S-1. Proyeksi, 21-33. Ansori, A. A. (2015). Dinamika Pernikahan pada Mahasiswa S-1 di Universitas Muhammadiyah Surakarta. 1-11. Hamali, S. (2015). Asketisme Dalam Islam Perspektif Psikologi Agama. Al- AdYaN/Vol.X, No2, 203. Marlina, N. (2013). Hubungan antara tingkat pendidikan orangtua dan kematangan emosi dengan kecenderungan menikah dini. Empathy. 2 (1). Marsela, D. J. (2017). Studi Kasus Terhadap Mahasiswa yang Menikah Saat Menempuh Masa Kuliah. Jurnal Tarbawi, Vol. 13, No. 02. Pujihartati, S. H. (2010). Fenomena Nikah Siri di Kalangan Mahasiswa dan Dampaknya terhadap Perempuan. Jurnal Sosiologi DiLeMa, 41-48. Skripsi: Kusuma, A. N. (2013). Perilaku Asketisme Duniawi Komunitas Hindu Di Kecamatan Senduro Kabupaten Lumajang. Universitas Jember. Muji, I. K. (2013). Motivasi Pengambilan Keputusan Menikah di Kalangan Mahasiswi Jurusan Psikologi Angkatan 2009. Universitas Pendidikan Indonesia.